GOOD ENGLISH TEACHING METHODOLOGY FOR JUNIOR HIGH SCHOOL STUDENTS - Ana Elvia Jakfar (Proceedings of ISELT FBS Universitas Negeri Padang, 2013)
Teaching methodology has become popular in teaching and learning activities in classroom. It also became the major thing included in lesson plan. Teaching methodology used in class room is an action to attain the purpose for each subject matter. Appropriate teaching methodology will make teaching activities more effective, and make students learn better. Hence, this condition will be an important aspect of the success of teaching and learning activities. However, finding an appropriate teaching method for both students and teachers are easily said than done. There are many factors that need to be considered in determining the appropriate teaching methodology. This presentation aims at reporting a research result that investigated some schools toward appropriate teaching English methodology for junior high school students. Research was conducted in some junior high school with interviewing and spreading questionnaires. The expected research result aims to find the appropriate method in teaching for junior high school students and be able to become a good suggestion for local government(s) to create this research result to be done for several years to come. This research result also expected to become a foundation for another researchers for doing the next same activity, so that our teaching in English subject will acquire useful input in enhancing the quality for both teaching for teachers and learning for students.